2014
DOI: 10.1111/joa.12237
|View full text |Cite
|
Sign up to set email alerts
|

Cellular proliferation in the nasal septal cartilage of juvenile minipigs

Abstract: The growth of the nasal septal cartilage is believed to be a driving force of midfacial growth. Cellular proliferation is an important contributor to growth of the cartilage, but this factor has been rarely investigated. The current study was undertaken to assess the proliferation and cellular density in the septal cartilage of fast-growing juvenile minipigs. Six minipigs averaging 4.4 ± 1 months old were injected with 5′-bromo-2′-deoxyuridine (BrdU), a thymidine analog, 24 h before death. The septal cartilage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Their evidence draws a distinction between septal growth relating to endochondral ossification at the PSept and ESept, which proceeds similarly to that of epiphyseal plates, and interstitial growth of cartilage more anteriorly. They concluded that the latter was more significant to septal length increase in young postnatal mice, and Al Dayeh and Herring () later confirmed the relationship of proliferation to midfacial growth in minipigs. Although we have no reason to discount the prolonged importance of interstitial cartilage growth at later ages, our findings suggest cartilage growth in the context of endochondral ossification is pronounced in the perinatal period of most if not all perinatal primates.…”
Section: Discussionmentioning
confidence: 91%
“…Their evidence draws a distinction between septal growth relating to endochondral ossification at the PSept and ESept, which proceeds similarly to that of epiphyseal plates, and interstitial growth of cartilage more anteriorly. They concluded that the latter was more significant to septal length increase in young postnatal mice, and Al Dayeh and Herring () later confirmed the relationship of proliferation to midfacial growth in minipigs. Although we have no reason to discount the prolonged importance of interstitial cartilage growth at later ages, our findings suggest cartilage growth in the context of endochondral ossification is pronounced in the perinatal period of most if not all perinatal primates.…”
Section: Discussionmentioning
confidence: 91%
“…Degree of mineralization of cancellous and cortical bone in the mandibular condyle plateaus at 40–60 weeks (Willems et al, ), providing a general idea of peak skeletal growth in the skull. Despite these studies having been conducted on domesticated pigs, skull growth in minipigs generally tracks the trajectory of domesticated pigs (Al Dayeh and Herring, ). Thus, depending on the growth rates of the model organism, 8 weeks may be insufficient to detect an osteogenic response.…”
Section: Discussionmentioning
confidence: 99%
“…The seven studies 10,[16][17][18]20,22,23 included in this review are pertaining to the midfacial growth, septopremaxillary traction system and the SPL resection in experimental animal models. The included studies comprises of two observational and five interventional studies.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The included studies comprises of two observational and five interventional studies. 10,[16][17][18][20][21][22][23]…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation